8m-2(m-3)=

Simple and best practice solution for 8m-2(m-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8m-2(m-3)= equation:


Simplifying
8m + -2(m + -3) = 0

Reorder the terms:
8m + -2(-3 + m) = 0
8m + (-3 * -2 + m * -2) = 0
8m + (6 + -2m) = 0

Reorder the terms:
6 + 8m + -2m = 0

Combine like terms: 8m + -2m = 6m
6 + 6m = 0

Solving
6 + 6m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 6m = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 6m = 0 + -6
6m = 0 + -6

Combine like terms: 0 + -6 = -6
6m = -6

Divide each side by '6'.
m = -1

Simplifying
m = -1

See similar equations:

| y=61+-1x | | 5n+n+10=28 | | 2x+1-x+2= | | f(x)=x^2+9x-1f(x+6) | | 9x+6=4x+101 | | 8(2K-1)=4k-28 | | -5=-2+l | | 9(2y-8)-(2y+2)= | | f(x+6)=x^2+9x-1 | | (176-y)=(115+x) | | 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= |

Equations solver categories